멀미 완화를 위한 비침습적 및 비약리적 방법 비교 및 평가 - 박승원; 최준원; 남상훈; 최여은; 이강인; 정면규; 신태민; 김한성; Park, Seung Won; Choi, Jun Won; Nam, Sanghoon; Choi, Yeo Eun; et al. (Journal of biomedical engineering research, 2021)
Purpose: The purpose of this study is to present a way to alleviate motion sickness(MS) by stimulating acupoint through PEMFs, and to assess the effectiveness of PEMFs against stimulation previously used to stimulate acupoint using biosignal evaluations and surveys. Materials and Methods: Thirteen healthy men participated in the experiment. MS was induced in the participants, and MS relief stimulation was applied for 30 minutes. There were 4 types of MS relief stimulation, and Sham, Reliefband, Transcutaneous electrical nerve stimulation(TENS), and Pulsed electromagnetic fields stimulation(PEMFs) were used. The biosignals were measured during 30 minutes of applying MS relief stimulation, and the symptoms of MS were evaluated through a questionnaire survey. The measured biosignals are Electrocardiogram(ECG), Electrodermal activity(EDA), Respiration, Skin temperature(SKT), and Electrogastrogram(EGG). A one-way ANOVA test was performed for the rate of change by stimulation for MS relief over time. Results: Participants who were stimulated had a sharp decrease in MS symptoms. Biosignals were analyzed to evaluate autonomic nervous system activity, and the parasympathetic nervous system could be activated through stimulation. Conclusion: TENS and PEMFs were more effective in relieving MS symptoms than Reliefband. It is believed that PEMFs will be effective in consideration of the comfort of participants to be applied to actual vehicles, and studies to further verify the effects of PEMFs on MS should be conducted.